1997
DOI: 10.1677/joe.0.1550151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid state on lipid peroxidation, antioxidant defences, and susceptibility to oxidative stress in rat tissues

Abstract: The effects of altered thyroid states on lipid peroxidation, antioxidant capacity, and susceptibility to oxidative stress of rat tissues were examined. Hypothyroidism was induced by administering methimazole in drinking water for 15 days. Hyperthyroidism was elicited by a 10-day treatment of hypothyroid rats with tri-iodothyronine (10 micrograms/100 g body weight). In tissues of hypothyroid rats the lipid peroxidation was not modified, whereas in hyperthyroid rats lipid peroxidation increased in liver and hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
188
5
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 34 publications
26
188
5
2
Order By: Relevance
“…In addition, Kupffer cells isolated from acutely T 3 -treated rats exhibited upregulation of UCP2 mRNA, which may limit mitochondrial ROS production by these cells (30). Consequently, T 3 -induced ROS production is associated with diminution in antioxidant defenses (28,(31)(32)(33), thus increasing the oxidative stress status in the liver with enhancement of hepatic lipid peroxidation (22,28,(34)(35)(36), protein carbonylation (37), and DNA oxidation (38). This pro-oxidant state induced in the liver of experimental animals by thyroid hormone administration is considered as a mild redox alteration, considering the lack of occurrence of morphological changes in liver parenchyma, except for significant hyperplasia and hypertrophy of Kupffer cells ( Fig.…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%
“…In addition, Kupffer cells isolated from acutely T 3 -treated rats exhibited upregulation of UCP2 mRNA, which may limit mitochondrial ROS production by these cells (30). Consequently, T 3 -induced ROS production is associated with diminution in antioxidant defenses (28,(31)(32)(33), thus increasing the oxidative stress status in the liver with enhancement of hepatic lipid peroxidation (22,28,(34)(35)(36), protein carbonylation (37), and DNA oxidation (38). This pro-oxidant state induced in the liver of experimental animals by thyroid hormone administration is considered as a mild redox alteration, considering the lack of occurrence of morphological changes in liver parenchyma, except for significant hyperplasia and hypertrophy of Kupffer cells ( Fig.…”
Section: T 3 -Induced Enhancement Of Liver O 2 Consumption and Oxidatmentioning
confidence: 99%
“…Findings about stress oxidative and activity of antioxidants in hypothyroidism are limited and controversial. There are some data that show in patients with hypothyroidism, oxidative stress, is increased (Lampka et al 2006;Sarandol et al 2005), decreased (Venditti et al 1997) or remain unchanged (Coria et al 2009). In agreement with the results of the current study, Reddy, et al demonstrated that the serum level of MDA and GPx activity increase in hypothyroid and subclinical hypothyroid patients (Reddy et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The previous biochemical studies carried out in animals by inducing hyperthyroidism show products of lipid peroxidation as indicators of oxidative stress in case of thyroid dysfunction, which are indirect markers of ROS generation (1,4,7,10,21). Moreover, in many cases, lipid peroxidation is a secondary phenomenon (25) and this does not therefore directly indicate an important role for oxidative stress in the disease concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are the major regulators of oxidative energy metabolism (1) at the level of the mitochondrion (2) inducing increase in oxygen consumption (3) and heat production in mammalian tissues (4,5) and are responsible for increased metabolic rate (6) in hyperthyroidism. Therefore, excess secretion of thyroid hormone or hyperthyroidism leads to hypermetabolic state, causing accelerated mitochondrial electron transport that could enhance generation of reactive oxygen species (ROS), thereby leading to oxidative stress.…”
mentioning
confidence: 99%